Levofloxacin-Associated Neurotoxicity in a Patient with a High Concentration of Levofloxacin in the Blood and Cerebrospinal Fluid - Masashi Nishikubo (Antibiotics, 2019)
Neurotoxicity is a rare and intolerable adverse effect associated with levofloxacin therapy, whose diagnosis has mostly been reported based on medical history rather than quantitative measures in the blood. We report a 68-year-old man with levofloxacin-associated encephalopathy and myoclonus with high levels of levofloxacin in the blood and cerebrospinal fluid. After hemodialysis, these decreased, and his symptoms rapidly improved. An electroencephalogram was also normal. This case showed the concentration of levofloxacin to be clearly related to levofloxacin-associated neurotoxicity. Therefore, an estimation of its concentration may contribute to accurate diagnosis.